Interaction between Simian Virus 40 Major Capsid Protein VP1 and Cell Surface Ganglioside GM1 Triggers Vacuole Formation - Yong Luo (American Society for Microbiology, 2016)
ABSTRACT Simian virus 40 (SV40), a polyomavirus that has served as an important model to understand many aspects of biology, induces dramatic cytoplasmic vacuolization late during productive infection of monkey host cells. Although this activity led to the discovery of the virus in 1960, the mechanism of vacuolization is still not known. Pentamers of the major SV40 capsid protein VP1 bind to the ganglioside GM1, which serves as the cellular receptor for the virus. In this report, we show that binding of VP1 to cell surface GM1 plays a key role in SV40 infection-induced vacuolization. We previously showed that SV40 VP1 mutants defective for GM1 binding fail to induce vacuolization, even though they replicate efficiently. Here, we show that interfering with GM1-VP1 binding by knockdown of GM1 after infection is established abrogates vacuolization by wild-type SV40. Vacuole formation during permissive infection requires efficient virus release, and conditioned medium harvested late during SV40 infection rapidly induces vacuoles in a VP1- and GM1-dependent fashion. Furthermore, vacuolization can also be induced by a nonreplicating SV40 pseudovirus in a GM1-dependent manner, and a mutation in BK pseudovirus VP1 that generates GM1 binding confers vacuole-inducing activity. Vacuolization can also be triggered by purified pentamers of wild-type SV40 VP1, but not by GM1 binding-defective pentamers or by intracellular expression of VP1. These results demonstrate that SV40 infection-induced vacuolization is caused by the binding of released progeny viruses to GM1, thereby identifying the molecular trigger for the activity that led to the discovery of SV40. IMPORTANCE The DNA tumor virus SV40 was discovered more than a half century ago as a contaminant of poliovirus vaccine stocks, because it caused dramatic cytoplasmic vacuolization of permissive host cells. Although SV40 played a historically important role in the development of molecular and cellular biology, restriction mapping, molecular cloning, and whole-genome sequencing, the basis of this vacuolization phenotype was unknown. Here, we show that SV40-induced vacuolization is triggered by the binding of the major viral capsid protein, VP1, to a cell surface ganglioside receptor, GM1. No other viral proteins or virus replication is required for vacuole formation. Other polyomaviruses utilize different ganglioside receptors, but they do not induce vacuolization. This work identifies the molecular trigger for the phenotype that led to the discovery of this important virus and provides the first molecular insight into an unusual and enigmatic cytopathic effect due to virus infection.